Accumulative effect of food residues on intestinal gas production. Issue 11 (25th August 2015) - Mego, M.; Accarino, A.; Malagelada, J.‐R.; Guarner, F.; Azpiroz, F.
Abstract Background As mean transit time in the colon is longer than the interval between meals, several consecutive meal loads accumulate, and contribute to colonic biomass. Our aim was to determine the summation effect of fermentable food residues on intestinal gas production. Methods In eight healthy subjects, the volume of endogenous intestinal gas produced in the intestine over a 4‐h period was measured by means of a wash‐out technique, using an exogenous gas infusion into the jejunum (24 mL/min) and collection of the effluent via a rectal Foley catheter. The exogenous gas infused was labeled (5% SF6) to calculate the proportion of endogenous intestinal gas evacuated. In each subject, four experiments were performed ≥1 week apart combining a 1‐day high‐ or low‐flatulogenic diet with a test meal or fast. Key Results Basal conditions: on the low‐flatulogenic diet, intestinal gas production during fasting over the 4‐h study period was 609 ± 63 mL. Effect of diet: during fasting, intestinal gas production on the high‐flatulogenic diet was 370 ± 146 mL greater than on the low‐flatulogenic diet (p = 0.040). Effect of test meal: on the low‐flatulogenic diet, intestinal gas production after the test meal was 681 ± 114 mL greater than during fasting (p = 0.001); a similar effect was observed on the high‐flatulogenic diet (599 ± 174 mL more intestinal gas production after the test meal than during fasting; p = 0.021). Conclusions & Inferences Our data demonstrate temporal summation effects of food residues on intestinal gas production. Hence, intestinal gas production depends on pre‐existing and on recent colonic loads of fermentable foodstuffs.